Piston connecting rod code detection and matching system using image processing and OCR (International Journal of Engineering and Computer Science, 2017)
In piston manufacturing company piston connecting rod divided into two parts and both parts have same batch number printed on it, now matching of this batch number performing manually so this is very tedious job and time consuming. So there is need for developing one system, “Piston connecting Code Matching and Detection System” to simplify this job and increase the productivity. Image Processing [IP] And Optical Character Recognition [OCR] is closely related term to each other. Image processing is any form of signal processing for which the input is an image file, such as a photograph or video frame; the output of image processing may be either an image or a set of characteristics or parameters related to the image and the Optical character recognition is the mechanical or electronic conversion of scanned or photographed images of typewritten or printed text into machine-encoded computer-readable text.